Advances in Affective and Pleasurable Design Proceedings of the AHFE 2016 International Conference on Affective and Pleasurable Design, July 27-31, 2016, Walt Disney World®, Florida, USA - Chung, WonJoon; Shin, Cliff Sungsoo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses the latest advances in affective and pleasurable design. It reports on important theoretical and practical issues, covering a wealth of topics, including aesthetics in product and system design, design-driven innovation, affective computing, evaluation tools for emotion, Kansei engineering for products and services, and many more. This timely survey addresses experts and industry practitioners with different backgrounds, such as industrial designers, emotion designers, ethnographers, human-computer interaction researchers, human factors engineers, interaction designers, mobile product designers, and vehicle system designers. Based on the AHFE 2016 International Conference on Affective and Pleasurable Design, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, the book represents an inspiring guide for all researchers and professionals in the field of design.
Design of Human Interface and Affective Communication -- Kawaii/ Affective Value Creation -- Affective/Emotion in Design Education (ADE) -- Design for Smart Environments and Well Living -- Emotional Engineering -- Empathetic Design -- Designing Affective, and Pleasurable Interactions.
Keywords: Computational intelligence; Engineering design; Emotions; Industrial engineering; Production engineering; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Engineering Design; Emotion; Industrial and Production Engineering; User Interfaces and Human Computer Interaction